Transferring Information Literacy Practices - Leung, Billy Tak Hoi.; Xie, Jingzhen; Geng, Linlin; Pun, Priscilla Nga Ian.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on information literacy for the younger generation of learners and library readers. It is divided into four sections: 1. Information Literacy for Life; 2. Searching Strategies, Disciplines and Special Topics; 3. Information Literacy Tools for Evaluating and Utilizing Resources; 4. Assessment of Learning Outcomes. Written by librarians with wide experience in research and services, and a strong academic background in disciplines such as the humanities, social sciences, information technology, and library science, this valuable reference resource combines both theory and practice. In today's ever-changing era of information, it offers students of library and information studies insights into information literacy as well as learning tips they can use for life.
Preface -- Acknowledgements -- Chapter 1 Information Literacy for Life -- Chapter 2 Searches Strategies, Disciplines and Special Topics -- Chapter 3 Resource Discovery Tools and Multi-disciplinary Databases -- Chapter 4 Information Literacy General Resources, Tools and How to Access Them -- Chapter 5 Information Literacy Resources in Science -- Chapter 6 Information literacy resources in the social sciences -- Chapter 7 Search Engines -- Chapter 8 Developing Information Literacy Skills with Various Tools -- Chapter 9 Assessment of Learning Outcomes for Information Literacy -- Appendix A Online Tutorials for Information Literacy Tools -- Appendix B Standards and Documents for Assessing Information Literacy -- Appendix C Selected Instruments for Assessment of Information Literacy -- Index.
Keywords: Computational linguistics; Library science; Computer networks .; Lexicology; Computational Linguistics; Library Science; Computer Communication Networks; Lexicolopgy / Vocabulary